Sport Betting and Mental Health Among Undergraduates of Rev. Fr. Moses Orshio Adasu University Makurdi Nigeria: The Mediating Role of Frustration - Idoko Raymond Oogwu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
Mental health is important for maximal functioning especially for students as it necessary for high academic performance. To this end, this study investigated the mediating role of frustration in sport betting and mental health among undergraduates of Rev. Fr. Moses Orshio Adasu University Makurdi Nigeria. Cross-sectional survey design was used and a sample of 394 students were sampled using multi-stage sampling technique, which was determined using Taro Yamane formula for sample size determination. Among the sampled students, 296 (74.9%) were male while 99 (25.1%) were female, and their age ranged from 18 – 33 years (with average age of 24.47; SD = 4.11). Sports Betting Scale, General Health Questionnaire (GHQ-12) and Frustration Scale were used for data collection. Four hypotheses were formulated and tested and result from the first hypothesis showed that there was a significant influence of sports betting on mental health among undergraduates of Rev. Fr. Moses Orshio Adasu University, Makurdi. From the second hypothesis, it was found that there was a significant influence of frustration on mental health among undergraduates of Rev. Fr. Moses Orshio Adasu University, Makurdi. Finding from hypothesis three showed that frustration significantly mediated the relationship between sports betting and mental health among undergraduates of Rev. Fr. Moses Orshio Adasu University, Makurdi. From the fourth hypothesis, it was found that all the independent variables (sports betting and frustration) significantly and jointly influenced mental health among undergraduates of Rev. Fr. Moses Orshio Adasu University, Makurdi. The findings were discussed in relation to other findings and conclusions were drawn. It was recommended among others that there should be campuswide awareness programs on the psychological risks associated with sports betting, emphasizing its impact on mental health and promoting healthier recreational activities